Nalar Kritis Pemikiran Omar Mohammad Al-Toumy Al-Syaibany dan Relevansinya dengan Pendidikan Bahasa Arab Berbasis MBKM - Wahyu Hanafi Putra; Maragustam Siregar (Institut Agama Islam Negeri Metro, 2023)
This study aims to describe the critical thinking of Al-Syaibany and its relevance to MBKM-based Arabic Language Education. This research is qualitative with a library research model. The results of the study show, first, that the implementation of Merdeka Learning is by the nature of the Islamic education curriculum, its characteristics, and its objectives. Every activity students study is a derivative of a planned curriculum. Second, the MBKM curriculum paradigm leads to the formation of students' knowledge of critical thinking and students' Arabic language skills. Two steps can be formed with the conditions of the learning environment, which can make students self-aware always to learn. Third, the design of the MBKM curriculum in the PBA Study Program is a reconstruction of the KKNI 2016.